Analisis Resiko Musculosceletal Disorder Pada Pengguna Laboratorium Ergonomi dan Perancangan Sistem Kerja Teknik Industri Universitas Muria Kudus - Akh Sokhibi (JURNAL REKAYASA SISTEM INDUSTRI, 2018)
Practicum in the laboratory of a university is not widely realized that it can have an ergonomic disorder (ergonomic disorder). This ergonomic disorder risk study was conducted on 56 students using Ergonomic Laboratory and System Working System of Muria Kudus University.The method used in this research is descriptive quantitative research with survey and observation instrument to analyze the risk of the occurrence of Musculosceletal Disorder (Ergonimic Disorder). Weighting and scores as well as statistical tests of contingency coefficients are used to determine the relationship level of risk with the incidence of Musculosceletal Disorder (Ergonimic Disorder).The results of this research is indicate that in the population who conducted high activity in the laboratory was 55.4% and in the population who were doing moderate activity in the laboratory of 44.6%. In other variables known are ergonomic disorders of 43% and no ergonomic disturbance disorder of 57%. While for statistical test result contingency coefficient equal to 0,26. The conclusion of this research is that facilities and attitude not ergonomic and less maximal socialization of K3 can cause complaint of ergonomic disorder at user of Mechanical Engineering Laboratory of Muria Kudus University